Gambaran Karakteristik dan Pengetahuan Relawan MDMC (Muhammadiyah Disaster Management Center) Tentang Triage Bencana di Kabupaten Sragen - Bella Septia Ningsih; Tri Susilowati (Calory Journal Medical Laboratory Journal, 2024)
Muhammadiyah Disaster Management Centre or MDMC is engaged in disaster management activities and triage systems. Information related to triage at MDMC Sragen Regency was obtained in 2019. Most volunteers had a basic understanding of disaster triage which was sufficient and indicated a need for knowledge and skills updates. The Objective of the Research; to determine the description of characteristic and knowledge of MDMC (Muhammadiyah Disaster Management Centre) volunteers about disaster triage in Sragen district. Methods; this type of research uses descriptive methods with a population 98 people sampling 50 respondents. Research instruments using questionnaires in the form of google forms with data analysis using univariate analysis. Results; the results showed that the characteristics of volunteers were male as many as 32 respondents (64.0%), in the age range of 17-25 years as many as 31 respondents (62.0%), with a high shcool/vocational education level as many as 31 respondents (62.0%) and had been a member of MDMC for 1-3 years as many as 28 respondents (56.0%). Then the results of volunteer knowledge in the moderate category as many as 35 repondents (70.0%). Summary; description of the characteristics and knowledge of MDMC volunteers about disaster triage in Sragen district the suffficient category.